In Vitro Evaluation of Aortic Insufficiency With a Rotary Left Ventricular Assist Device. Issue 9 (1st August 2013) - Gregory, Shaun D.; Stevens, Michael C.; Wu, Eric; Fraser, John F.; Timms, Daniel
Abstract: Aortic insufficiency (AI) is usually repaired prior to rotary blood pump (RBP) implantation but can develop during support due, in part, to the sustained RBP‐induced high pressure gradient across the aortic valve. Repair of the aortic valve before or during RBP support predisposes these critically ill patients to even higher risks. This study used an in vitro mock circulation loop to identify the severity of AI and/or left heart failure (LHF) that might benefit from valve repair while investigating RBP operating strategies to reduce the hemodynamic influence of AI. Reproduction of AI with RBP‐supported LHF reduced device efficiency, particularly in the more severe cases of AI and LHF. The requirement for repair or closure of the aortic valve was demonstrated in all conditions other than those with only mild AI. When a sinusoidal RBP speed pulse was induced, small changes in systemic flow rate and regurgitant volume were observed with all degrees of AI. Variation of the pulse phase delay only resulted in minor changes to systemic flow rate, with a maximum difference of 0.17 L/min. Although the clinical implications of these small changes may be insignificant, changes in systemic flow rate and transvalvular pressure were shown when the sinusoidal RBP speed pulse was applied with no AI. In these cases, transvalvular pressure was reduced by up to 8% through sinusoidal copulsation of the RBP, which may prevent or delay the onset of AI. This in vitro study suggests that surgical intervention is required with moderate or worse AI and that RBP operating strategies should be further explored to delay the onset and reduce the harmful effects of AI.